Temu Kembali Citra pada Kue Tradisional berdasarkan Ekstraksi Fitur Color Histogram dan Color Moment menggunakan Algoritme Perhitungan Jarak Minkowski - Andina Dyanti Putri; Yuita Arum Sari; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Traditional cookies represent every single place in our country with its uniqueness. We can find the information on those culinary through various media such as books or the internet. It is straightforward if we know the name of the foods. However, the limitation of one's knowledge will bring different problems in acquiring the information, especially if it is text-based. The solution to that problem is to use Content-Based Image Retrieval (CBIR), a technique that automatically uses an image as a query and display a series of the similar image just like the query. We use feature extraction in CBIR, which is also a fundamental part of Image Analysis. The feature extraction is used Color Histogram and Color Moment. This research is using Minkowski distance calculation with following values: p = 1, p = 2, p = 3 and p = 5. The value of p = 3 in Minkowski distance calculation gives the best result to the combination of these two features is valued at 0,720498. The MAP average value which is acquired from top K-rank: k = 5, k = 10, k = 15, k = 20, and k = 25, is valued at 0,7119 for the features combination. We can conclude from this result that the feature extraction Color Histogram and Color Moment gives an excellent result for traditional cookies image analysis.